Parental origin of the deletion del(20q) in Shwachman‐Diamond patients and loss of the paternally derived allele of the imprinted L3MBTL1 gene. Issue 1 (21st September 2016) - Nacci, Lucia; Valli, Roberto; Maria Pinto, Rita; Zecca, Marco; Cipolli, Marco; Morini, Jacopo; Cesaro, Simone; Boveri, Emanuela; Rosti, Vittorio; Corti, Paola; Ambroni, Maura; Pasquali, Francesco; et al.
Abstract : Shwachman–Diamond syndrome (SDS) (OMIM 260400) is a rare autosomal recessive disease characterized by exocrine pancreatic insufficiency, skeletal, and hematological abnormalities and bone marrow (BM) dysfunction. Mutations in the SBDS gene cause SDS. Clonal chromosome anomalies are often present in BM, i(7)(q10) and del(20q) being the most frequent ones. We collected 6 SDS cases with del(20q): a cluster of imprinted genes, including L3MBTL1 and SGK2 is present in the deleted region. Only the paternal allele is expressed for these genes. Based on these data, we made the hypothesis that the loss of this region, in relation to parental origin of deletion, may be of relevance for the hematological phenotype. By comparing hematological data of our 6 cases with a group of 20 SDS patients without evidence of del(20q) in BM, we observed a significant difference for Hb levels ( P < 0.012), and a difference slightly above the significance level for RBC counts ( P < 0.053): in both cases the values were higher in patients with del(20q). We also report preliminary evidence for an increased number of BFU‐E colonies in cases with paternal deletion, data on the presence of the deletion in colonies and in mature circulating lymphocytes. © 2016 Wiley Periodicals, Inc.